Incidence of Droughts and its Impact on Food Production in Rajasthan - Rao, G G.S.N; Ramakrishna, Y S; Ramana Rao, B V; Purohit, R S (Annals of Arid Zone, 2016)
Incidence and spread of drought over Rajasthan during the years 1972, 1974 and 1979, were analysed on the basis of departures from the normal aridity index during different months of the southwest monsoon season. Productivity of pearlmillet and pulses was considerably affected by drought conditions. The impact of drought on fall in productivity of these crops is more pronounced in western Rajasthan than in eastern Rajaslhan. The study brought out that the variations in the productivity of the rainfed crops can he explained satisfactorily by the pattern of incidence and the spread of droughts.